COMPARATIVE STUDY OF THE LEVEL OF DENTAL HYGIENE KNOWLEDGE AMONG INDIVIDUALS WITH HEARING IMPAIRMENT - Yuldashev F.F., Kuryozov A.K. (Central Asian Journal of Medicine, 2025)
The study is devoted to assessing the level of dental hygiene knowledge among individuals with hearing impairment. The data obtained from a survey of 300 respondents was analyzed. The frequency of visiting the dentist, awareness of professional hygiene, use of additional care products, and motivation to receive recommendations were assessed. Insufficient knowledge, low frequency of use of additional hygiene products, and poor awareness of the role of dental hygienists were established. The results emphasize the need to develop targeted preventive programs adapted to the needs of this group.